Modelling fluid flow in carbon fibre porous media based on X-ray microtomography and lattice Boltzmann method. (15th November 2022) - Li, Yong; Chi, Yanmeng; Zhao, Chaojie; Miao, Yanan; Han, Shanling; Chen, Long
Abstract: Carbon fibre media possess complex internal porous structures; the microstructures are vital and can impact the efficiency of fluid flow and mass transfer. In this study, X-ray microtomography (XMT) and the lattice Boltzmann method (LBM) was employed to reconstruct the authentic three-dimensional (3D) pore structures of carbon fibre media and simulate its fluid flow. The effects of fluid properties and boundary conditions were elucidated. Results demonstrated that the flow velocity increased as the displacement differential pressure increased, but decreased as the fluid kinematic viscosity increased. The critical values of differential pressure and viscosity were 4.0106 Pa and 0.0101 m 2 /s, respectively. The simulation results of the average volume velocity revealed that three boundary conditions had extremely small relative errors of 0.0037 % depending on the carbon fibre material. When the Kozeny–Carman constant (KC, k ) was 3.5, the relative error of permeability between the predicted values and the simulated values decreased with increasing porosity. When the porosity was 54.069 %, the relative error decreased to 4.18 %. The fractal model revealed worse results for the permeability prediction of carbon fibre porous media, and the relative error between the simulated and predicted values was 50.40 % when the porosity was 45.585 %.